1997
DOI: 10.1016/s0092-8674(00)81926-1
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Metalloelastase Is Responsible for the Generation of Angiostatin in Lewis Lung Carcinoma

Abstract: To determine the mechanism responsible for the in vivo production of angiostatin that inhibits growth and metastasis in Lewis lung carcinoma (3LL), we implanted 3LL variant cells into the subcutis of syngeneic C57BL/6 mice. The tumors were infiltrated by macrophages and expressed high levels of steady-state mRNA for metalloelastase (MME). Successive passages (more than three) of cultures established from the tumors resulted in complete depletion of macrophages; steady-state MME mRNA, elastinolytic activity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
284
1
6

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(294 citation statements)
references
References 44 publications
3
284
1
6
Order By: Relevance
“…It was recently shown (Di-Pietro et al, 1993) that activated highly angiogenic macrophages produce the angiogenic inhibitor thrombospondin-1, which shows a complex angiogenic role of macrophages defined by positive and negative regulators. In a recent study (Dong et al, 1997), angiostatin expression by Lewis lung subcutaneously growing tumours required the presence of macrophages and was directly correlated with macrophage metalloelastinolytic activity. Fibroblasts have also a role in angiogenesis regulation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It was recently shown (Di-Pietro et al, 1993) that activated highly angiogenic macrophages produce the angiogenic inhibitor thrombospondin-1, which shows a complex angiogenic role of macrophages defined by positive and negative regulators. In a recent study (Dong et al, 1997), angiostatin expression by Lewis lung subcutaneously growing tumours required the presence of macrophages and was directly correlated with macrophage metalloelastinolytic activity. Fibroblasts have also a role in angiogenesis regulation.…”
Section: Discussionmentioning
confidence: 94%
“…It would be of interest to examine whether the combination of IFN-oc and GM-CSF restores the fibroblast and macrophage intratumoral activity and prevents tumour progression in refractory metastatic non-small-cell lung cancer. The recent observation that GM-CSF-stimulated macrophages have enhanced metalloelastinolytic activity, which is required for tumour angiostatin production, further supports such a therapeutic approach (Dong et al, 1997).…”
Section: Discussionmentioning
confidence: 94%
“…Since MMP-12 is not only involved in lung tissue remodeling-associated diseases [35,37,41,46,50,[81][82][83][84][85][86][87][88][89], substantial efforts have been made to develop MMP-12 synthetic inhibitors. However, inhibiting a specific MMP is a difficult goal because of the high conservation between many MMPs in terms of overall 3D-structure, topology of the catalytic domain and requirement of specific amino-acid residues in the active site [90,91].…”
Section: Most Efficient Mmp-12 Chemical Inhibitorsmentioning
confidence: 99%
“…Several other substrates of MMP-12 have been described such as myelin basic protein, α1-antitrypsin [44] and tissue factor pathway inhibitor (TFPI) [45], plasminogen [46,47] and N-cadherin [48].…”
mentioning
confidence: 99%
“…It has been demonstrated that angiostatin can be generated by established human cell lines of melanoma, bladder, colon, cervical, breast, and ovarian carcinomas, 19 the CaP cell line PC-3, a pancreatic-cancer cell line, 20 as well as activated macrophages. 21,22 The proteolytic enzymes, u-PA, tPA, elastase, metalloproteinases (MMPs), 23 and prostate-specific antigen 24 can also be involved in angiostatin generation.…”
Section: Introductionmentioning
confidence: 99%